Engineered Bacteriophage T7 as a Potent Anticancer Agent in vivo - Hwang, Yoon Jung; Myung, Heejoon (Frontiers in Microbiology, 2020)
Oncolytic viruses (OVs) induce antitumor effect by both direct lysis of target cells and eliciting immunogenic response to the virus and ultimately to the target cells. These viruses are usually natural human pathogens. Bacteriophages are natural pathogens of bacteria that do not infect human and have greater advantages in safety, manipulation, and production over human viruses. We constructed an engineered bacteriophage T7 displaying a peptide, which targets murine melanoma cells and harbors a mammalian expression cassette of the cytokine granulocyte macrophage-colony stimulating factor (GM-CSF) in viral genomic DNA. The engineered phage was successfully transduced to B16F10 melanoma cells both in vitro and in vivo. GM-CSF was expressed from the transduced phage DNA. All mice treated with the phage intravenously survived for 25 days until the end of experiment, while only 40% of those not treated survived. During the 16 days of phage treatment, phage T7 displaying homing peptide and expressing GM-CSF inhibited tumor growth by 72% compared to the untreated control. Serum cytokine levels of IL-1α, TNF-α, and GM-CSF were seen to increase during the treatment. Immunohistochemical analysis of tumor tissue revealed infiltration by macrophages, dendritic cells (DCs), and CD8+ T cells. Migration of murine macrophages to bacteriophages was also observed in in vitro transwell assays in both time- and dose-dependent manners. Taken together, the recombinant bacteriophage T7 efficiently inhibited tumor growth by changing the tumor microenvironment and recruiting anti-tumor immune cells.